Calidad en servicios educativos mediante aplicación de Servqual, caso Universidad Técnica de Machala. - Jaén Banegas, Silvia Janine; Solano De La Sala Paladines, Jeanneth Gabriela (My University, 2018)
In the present work the SERVQUAL instrument was used to perform an analysis of the quality of service in a higher education institution, using descriptive statistics to analyze the dimensions that intervene in the expectations and perspectives of the students of administrative careers of the Technical University de Machala, which was considered as a case study. The objective was to evaluate the quality of service provided by a higher education institution. The methodology was of quantitative type, through a questionnaire, the same one that used the SERVQUAL model, applying a Likert scale of 5 points, 22 questions to know the expectations of the service and in the same way to know the perception of the service of the institution. The analysis carried out in the research consisted of descriptive analysis of the five dimensions (reliability, response capacity, safety, knowledge and attention, empathy, and tangible aspects), reliability analysis of the instrument using the cronbach alpha, and gap analysis. existing between the expectation of service versus the service received. The results were relevant, from the values obtained in the dimensions analyzed, we could find that reliability; security, knowledge and attention; empathy; and tangible aspects have a good consistency, that is, there is a high internal correlation between their items, both for the expectations and perspectives of the service. But the response capacity dimension, for expectations and perspectives is between 0.5 and 0.7, is considered a low reliability, this could be understood because these items seek to know what is the response capacity that the organization has at the moment of Provide a service. Regarding the gaps, negative values were obtained in all dimensions, this is because the expectations that students have in Higher Education institutions are very high, taking into account the changes and advances that are taking place at the level country, and the advances to which the institution is heading are always being projected.From the results obtained, it can be evidenced that there is a good perception on the part of the students about the institution, this was demonstrated taking into account that three of the five dimensions were with means superior to three, which shows a good quality in the service. Regarding expectations, they are very high, due to the changes that are taking place in the institution and in the rest of Ecuador's higher education institutions. As a priority aspect is visualized in the results that the aesthetics of the facilities is one of the points that give higher value to students in regard to quality of service. And it goes hand in hand with the dimensions because the tangible aspects are the ones that have the highest value in expectations, and in perception the dimension that has the greatest value on the part of the students is that of Security, knowledge and attention provided by the institution. Of the results obtained when applying the SERVQUAL in the institution of Higher Education, it expresses an average of the dimensions of 3.11 which indicates that the service is considered acceptable, but improvements can occur, especially in the dimensions of Reliability and Capacity of answer.
En el presente trabajo se usó el instrumento SERVQUAL para realizar un análisis de la calidad de servicio en una institución de Educación superior, usando estadística descriptiva para analizar las dimensiones que intervienen en las expectativas y perspectivas que tienen los estudiantes de carreras administrativas de la Universidad Técnica de Machala, que fue considerada como caso de estudio. El objetivo fue es evaluar la calidad de servicio brindado por una institución de educación superior. La metodología fue de tipo cuantitativa, a través de un cuestionario, el mismo que uso el modelo SERVQUAL, aplicando escala Likert de 5 puntos, 22 preguntas para conocer las expectativas del servicio y de igual forma para conocer la percepción del servicio de la institución. Los análisis realizados en la investigación consistieron en análisis descriptivos de las cinco dimensiones (fiabilidad; capacidad de respuesta; seguridad, conocimientos y atención; empatía; y aspectos tangibles), análisis de confiabilidad del instrumento mediante el alfa de cronbach, y análisis de la brecha existente entre la expectativa de servicio versus el servicio recibido. Los resultados fueron relevantes, de los valores obtenidos en las dimensiones analizadas, se pudo encontrar que fiabilidad; seguridad, conocimientos y atención; empatía; y aspectos tangibles tienen una buena consistencia, es decir existe alta correlación interna entre sus ítem, tanto para las expectativas y perspectivas del servicio. Pero la dimensión Capacidad de respuesta, para expectativas y perspectivas esta entre 0,5 y 0,7, se considera una fiabilidad baja, esto se podría entender debido a estos ítems buscan conocer cuál es la capacidad de respuesta que tiene la organización al momento de brindar un servicio. En lo que respecta a las brechas, se obtuvieron valores negativos en todas las dimensiones, esto se da porque las expectativas que tienen los estudiantes en las instituciones de Educación Superior son muy altas, teniendo en consideración los cambios y avances que se vienen dando a nivel país, y siempre se viene proyectando los avances a los cuales está encaminada la institución. De los resultados obtenidos, se puede evidenciar que existe una buena percepción por parte de los estudiantes acerca de la institución, esto se demostró tomando en consideración que tres de las cinco dimensiones fueron con medias superiores a tres, lo que evidencia una buena calidad en el servicio. En lo que refiere a las expectativas, las mismas son bien altas, debido a los cambios que se vienen dando en la institución y en el resto de instituciones de educación superior del Ecuador. Como aspecto prioritario se visualiza en los resultados que la estética de las instalaciones es uno de los puntos que mayor valoración le dan los estudiantes en lo que refiere a calidad de servicio. Y va de la mano con las dimensiones debido a que los aspectos tangibles son los que tienen mayor valoración en las expectativas, y en la percepción la dimensión que tiene mayor valoración por parte de los estudiantes es la de Seguridad, conocimientos y atención que brinda la institución. De los resultados obtenidos al aplicar el SERVQUAL en la institución de Educación Superior, expresa un promedio de las dimensiones de 3,11 lo que indica que se considera aceptable el servicio, pero pueden darse mejoras, en especial en las dimensiones de Fiabilidad y Capacidad de respuesta.
Keywords: CALIDAD; CALIDAD DE SERVICIO; SATISFACCIÓN; SERVQUAL